(untitled) (Proceedings of the YSU B: Chemical and Biological Sciences, 2018)
Based on available reagents: tetrahydrofurfuryl alcohol and tetrahydrofuran, the technologically easily implemented method of synthesis of the active component of the sex pheromone of Oriental Fruit Moth Grapholitha Molesta with predominant content of (Z)-dodec-8-enyl acetate by two synthon C8+C4 scheme was developed. The condensation stage of C4 and C8 was performed in the presence of dilithium tetrachlorocuprate.